2-Sulfonamidopyridine C-region analogs of 2-(3-fluoro-4-methylsulfonamidophenyl)propanamides as potent TRPV1 antagonists. Issue 6 (15th March 2016) - Ann, Jihyae; Ki, Yooran; Yoon, Suyoung; Kim, Myeong Seop; Lee, Jung-Un; Kim, Changhoon; Lee, Sunho; Jung, Aeran; Baek, Jisoo; Hong, Sunhye; Choi, Sun; Pearce, Larry V.; et al.
Graphical abstract: Abstract: A series of 2-sulfonamidopyridine C-region derivatives of 2-(3-fluoro-4-methylsulfonamidophenyl)propanamide were investigated as h TRPV1 ligands. Systematic modification on the 2-sulfonamido group provided highly potent TRPV1 antagonists. The N -benzyl phenylsulfonamide derivatives12 and23 in particular showed higher affinities than that of lead compound1 . Compound12 exhibited strong analgesic activity in the formalin pain model. Docking analysis of its chiral S -form12 S in our h TRPV1 homology model indicated that its high affinity might arise from additional hydrophobic interactions not present in lead compound1 S .